Level of gross motor skills in lower grade students at integrated Islamic elementary school - Basuki, Basuki; Maarif, Ilmul (Universitas Sebelas Maret, 2024)
Related to the research objectives in this case want to know the level of gross motor skills of students, and the type of quantitative descriptive research to describe the events that occur currently in the field, the population of this study is 78 lower grade SDIT students with purposive sampling technique in students aged between 7-9 years so that this study includes population research, data measurement with the TGMD-2 test component instrument. The results of locomotor movements of SDIT students fall into the category above the average of 19.23%, for manipulative movements of students with the average category there are 35.90%, and for gross motor shows the average category with the number (47.44%). This conclusion shows that the gross motor level of integrated Islamic elementary school students in the gross motor is in the average category.